Leveraging ChatGPT and Gemini to Support Teacher Creativity in Developing Digital Instructional Materials: A Literature Review - Baiq Oriza Januarlinda; Nurul Asmaya Fitria Hasanah; Baiq Anisya Nelahi Purnadya; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2026)
The rapid advancement of Large Language Models (LLMs), notably ChatGPT and Gemini, has significantly catalyzed educational innovation by enabling the rapid and adaptive creation of instructional content. This study analyzes the utilization of generative AI in bolstering teacher creativity for digital material development. Employing a narrative literature review approach, 17 relevant articles published between 2016 and 2025 were synthesized, sourced from Crossref, Google Scholar, and OpenAlex via the Publish or Perish application. The findings demonstrate that generative AI effectively assists teachers in designing learning media, instructional materials, and evaluation tools with greater efficiency. However, challenges such as infrastructure limitations, data validity concerns, and the imperative for human verification remain prevalent. The study concludes that integrating AI into content development must be accompanied by continuous digital literacy training and rigorous adherence to ethical standards.